2018
DOI: 10.1371/journal.pone.0196526
|View full text |Cite
|
Sign up to set email alerts
|

Circulating pentraxin 3 is positively associated with chronic hyperglycemia but negatively associated with plasma aldosterone concentration

Abstract: Pentraxin 3 (PTX3) is reported to be a vascular inflammation marker providing prognostic information of vasculopathy. Until today, however, the effect of aldosterone or oxidative stress on the regulation of PTX3 is unknown. In present study, we investigated to find regulative factors, especially aldosterone and oxidative stress, on PTX3. Serum PTX3 levels were measured in 75 patients (45 male and 30 women, aged 55.1±13.4 year-old (mean±SD)) with various endocrine disorders including 47 with diabetes, 24 with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 41 publications
(46 reference statements)
1
7
1
Order By: Relevance
“…This study also revealed that there was a highly significant correlation between glycemic control (HbA 1 c) and development of DN as HbA 1 c was elevated in the DN groups more than in the control and diabetic without DN groups. These results are in accordance with Takashi et al [8]. In agreement with Wang et al [12] and Uzun et al [9], this study showed that there is a highly significant correlation between FBG and 2hBBPG, and the development of DN.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This study also revealed that there was a highly significant correlation between glycemic control (HbA 1 c) and development of DN as HbA 1 c was elevated in the DN groups more than in the control and diabetic without DN groups. These results are in accordance with Takashi et al [8]. In agreement with Wang et al [12] and Uzun et al [9], this study showed that there is a highly significant correlation between FBG and 2hBBPG, and the development of DN.…”
Section: Discussionsupporting
confidence: 93%
“…This is in accordance with Wang et al [12] and Rutledge et al [19] who stated that there is a significant association between serum TGs and DN. In contrast to this study, Takashi et al [8] mentioned that there is no association between serum TGs and DN. However, this study revealed that there was no significant association between the development of DN with serum total cholesterol, HDL, and LDL.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…64 In a sample of patients with endocrine disorders, serum pentraxin-3 levels were negatively correlated with plasma aldosterone concentrations, suggesting that aldosterone may be a negative regulator of pentraxin-3. 65 However, there is conflicting evidence regarding the influence of pentraxin-3 on CVD due to pentraxin-3 having both beneficial and detrimental cardiovascular effects that are context dependent. 66…”
Section: Raasmentioning
confidence: 99%